(untitled) (Research, Society and Development, 2026)
Altered passive eruption (APE) is a clinical a developmental condition where the gingival margin fails to recede to the cemento-enamel junction, caused by excessive gum overlapping over the enamel limits, resulting in a short clinical crown. Minimally invasive surgical approaches using diode laser have been proposed for APE management due to their hemostatic properties and potential for improved postoperative comfort. The aim of this case report is to describe APE treated with diode laser-assisted gingivectomy and gingivoplasty combined with osteotomy. A 28-year-old systemically healthy female patient presented with esthetic complaint of excessive gingival display and short clinical crowns. Clinical and radiographic examinations revealed gingival enlargement associated with APE and vestibular exostoses, without signs of active periodontal disease. Initial therapy included oral hygiene conditioning and scaling and root planing. The treatment consisted of diode laser-assisted gingivectomy and gingivoplasty (980 nm, Therapy XT, DMC), combined with osteotomy and osteoplasty to reestablish biologic width and improve crown proportions. Postoperative photobiomodulation using low-level laser therapy was performed to support tissue healing. Clinical follow-up was performed weekly, with final evaluation at 90 days. The patient reported absence of postoperative pain, favorable healing pattern, and high satisfaction with the esthetic outcome. This case demonstrates that diode laser-assisted periodontal plastic surgery associated with osseous resective therapy may represent a conservative therapeutic approach for management of gingival excess associated with APE.